Aktivitas Antibakteri Fraksi Diklorometan dan N-Heksana Paku Sisik Naga (Drymoglossum piloselloides (L) Presl.) Terhadap Bakteri Staphylococcus aureus dan Salmonella typhi - Elvi Rusmiyanto Pancaning Wardoyo, Heriyati Siti Khotimah (Universitas Tanjungpura, 2016)
The potential use of dragon scales have been used by people in Kalimantan as anti-inflammatory drugs, oral thrush and toothache. Dragon scales (D. Piloselloides) is one of epiphytic plants in association with other plants. This study aims to determine the antibacterial activity of the dichloromethane and n-hexane fraction of dragon scales against S. aureus and S. typhi. The research was conducted from October to December 2015 in the Pharmaceutical Chemistry Laboratory Faculty of Medicine, Wood Technology Laboratory Faculty of Forestry, Chemistry Laboratory and Biology Laboratory Faculty of Mathematics and Natural Sciences, Tanjungpura University, Pontianak. Dichloromethane and n-hexane fraction were obtained from the fractionation of methanol extract. Furthermore, both fractions in TLC and chromatogram profiles were visualized using UV 254 and 336 nm. Antibacterial test of D. piloselloides fraction was done by paper disc diffusion method. The concentration used in this study was 0.25; 0.30 and 0.35 g/ml, and as a comparison, Ciprofloxasin 0.005 mg/ml used as a positive control. Antibacterial activity test of dichloromethane fraction of dragon scales has only the ability to inhibit S. aureus, whereas the n-hexane fraction has no antibacterial activity against S. aureus and S. typhi. TLC test results showed that the dichloromethane fraction contains flavonoids compounds, while the n-hexane fraction contains terpenoids compounds.